2019
DOI: 10.1007/s10826-018-01308-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management Support Intervention for Parents of Children with Developmental Disorders: The Role of Gratitude and Hope

Abstract: Objectives Many parents of children with developmental disabilities, including autism spectrum disorders and attention deficit disorders, experience poor well-being and increased anxiety and depression. Very few interventions directly target parents' needs. The peer-delivered HOPE Programme was designed to address this with six weekly group sessions focusing on self-management skills, including goal setting and expressing gratitude. Methods This pre-post study aimed to examine changes in anxiety, depression, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 65 publications
2
39
0
1
Order By: Relevance
“…64 To mitigate recovery-related perceptions, the online interactive elements as well as self-efficacy-enhancing features of SMArTVIEW R&R have been adapted from the Help to Overcome Problems (HOPE) and iHOPE programs based out of Coventry University. HOPE and iHOPE [65][66][67][68] are uniquely grounded in both positive psychology and cognitive behavioral therapy theory and incorporate evidence-based cognitive behavioral therapy and positive psychological activities such as goal setting and action planning, identifying personal strengths, scheduling activity and rest periods, mindfulness, relaxation training, and reviewing successes. Feasibility trials have shown that HOPE and iHOPE have the potential to improve important health-related quality of life outcomes for people living with and affected by a range of long-term conditions.…”
Section: Smartview Self-management Trainingmentioning
confidence: 99%
“…64 To mitigate recovery-related perceptions, the online interactive elements as well as self-efficacy-enhancing features of SMArTVIEW R&R have been adapted from the Help to Overcome Problems (HOPE) and iHOPE programs based out of Coventry University. HOPE and iHOPE [65][66][67][68] are uniquely grounded in both positive psychology and cognitive behavioral therapy theory and incorporate evidence-based cognitive behavioral therapy and positive psychological activities such as goal setting and action planning, identifying personal strengths, scheduling activity and rest periods, mindfulness, relaxation training, and reviewing successes. Feasibility trials have shown that HOPE and iHOPE have the potential to improve important health-related quality of life outcomes for people living with and affected by a range of long-term conditions.…”
Section: Smartview Self-management Trainingmentioning
confidence: 99%
“…Robust evidence shows mental health and well-being to be associated with person-specific characteristics (Benson, 2010; Landon et al, 2018; Martin et al, 2019). Among parents of children with autism, evidence suggests associations between higher levels of gratitude and hope with increased well-being and decreased depression (Martin et al, 2019), and between higher self-esteem and adaptive coping strategies, with higher well-being and reduced health problems (Landon et al, 2018).…”
mentioning
confidence: 99%
“…Robust evidence shows mental health and well-being to be associated with person-specific characteristics (Benson, 2010; Landon et al, 2018; Martin et al, 2019). Among parents of children with autism, evidence suggests associations between higher levels of gratitude and hope with increased well-being and decreased depression (Martin et al, 2019), and between higher self-esteem and adaptive coping strategies, with higher well-being and reduced health problems (Landon et al, 2018). Greater mindfulness has also been shown to be associated with reduced depression, anxiety, and stress, among parents of children with autism (Rayan & Ahmad, 2018) and, furthermore, such parents who received a mindfulness-based intervention have shown significantly improved depression and anxiety (Rayan & Ahmad, 2017), stress (Bazzano et al, 2015; Rayan & Ahmad, 2017) and well-being (Bazzano et al, 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations